A Study To Understand The Significance Of Platelet Indices In Type2 Diabetes Mellitus Patients In A Tertiary Care Hospital. - Prathipa, R.; Prathipaa, R.; Saranya Bai, S. (Journal of Neonatal Surgery, 2025)
Background: Type 2 Diabetes Mellitus (T2DM) is a global health challenge, affecting millions worldwide. This condition is associated with vascular complications due to endothelial dysfunction and platelet hyperactivity. Platelet indices, such as Mean Platelet Volume (MPV), Platelet Distribution Width (PDW), and Plateletcrit (PCT), have been recognized as potential biomarkers for platelet activity and predictors of vascular risk in T2DM. Methods: This prospective case-control study was conducted over three months (2024–2025) at the Department of Pathology, ACS Medical College and Hospital. A total of 124 participants were recruited, including 62 T2DM patients and 62 age- and gender-matched non-diabetic controls. Venous blood samples were analyzed for platelet indices and glycemic markers using automated analyzers. Statistical analysis included independent t-tests and Pearson correlation, with a significance threshold of p < 0.05. Results: T2DM patients exhibited significantly higher MPV (10.8 ± 0.9 fL vs. 9.1 ± 0.8 fL, p < 0.001), PDW (13.9 ± 1.7 fL vs. 12.5 ± 1.4 fL, p < 0.01), and PCT (0.28 ± 0.05% vs. 0.22 ± 0.03%, p < 0.001) compared to controls. Glycemic markers (FBS and HbA1c) were also elevated in T2DM patients. Strong positive correlations were observed between HbA1c and MPV (r = 0.68, p < 0.001) as well as PDW (r = 0.55, p < 0.01). Conclusion: Elevated platelet indices in T2DM patients reflect hyperactive platelet function and a prothrombotic state. These indices are strongly associated with poor glycemic control and may serve as cost-effective, accessible biomarkers for identifying patients at risk of vascular complications. Further studies are warranted to validate their clinical utility in diverse populations.